Hodnocení výkonnosti podniku - Rusnak, Alexandra (Vysoké učení technické v Brně. Fakulta podnikatelská, 2024)
Bakalářská práce je zaměřena na průzkum finanční situace podniku, hledání slabých stránek a opatření ke zlepšení finanční situace. Výkonnost podniku bude měřena pomocí finanční analýzy. V první kapitole budou zkoumány teoretické aspekty finanční analýzy, které budou aplikovány v kapitole druhé. Ve druhé kapitole budou po provedení výpočtů identifikována slabá místa v podniku. Třetí kapitola popisuje silné a slabé stránky společnosti pomocí SWOT-analýzy. Po určení směru růstu podniku jsou navržena opatření a provedeny výpočty.

The bachelor's thesis is focused on researching the financial situation of the company, finding weaknesses and measures to improve the financial situation. The performance of the business will be measured using financial analysis. The first chapter will examine the theoretical aspects of financial analysis, which will be applied in the second chapter. In the second chapter, after performing the calculations, weak points in the company will be identified. The third chapter describes the company's strengths and weaknesses using a SWOT analysis. After determining the direction of the company's growth, measures are proposed and calculations are made.
Evaluation of the Corporate Performance
Keywords: Finance; finanční výsledky; solventnost; likvidita; obchodní činnost; rentabilita; bankrot; akciová společnost; finance; financial results; solvency; liquidity; business activity; profitability; bankruptcy; joint-stock company